BIOLOGICALLY ACTIVE SUBSTANCES OF LAVANDULA X INTERMEDIA EMERIC EX LOISEL (LAMIACEAE) - A. E. Paliy; V. D. Rabotyagov (Фармация и фармакология (Пятигорск), 2016)
Data about qualitative and quantitative composition of biologically active substances (volatile and phenolic compounds) in water- ethanol extract of Lavandula x intermedia Emeric ex Loisel (Lamiaceae) cv. ‘Bora’ bred in Nikitsky Botanical Garden are presented in the article. Concentration of volatile compounds in Lavandin extract was 398 mg/dm3 and 51 components were identified. Main volatiles in Lavandin cv. «Bora» extract were linalyl acetate (36,9%) and linalool (33,5%). Content of phenolic compounds in water- ethanol extract of Lavandin was 945 mg/dm3 and 14 components were found out. Among the variety of Lavandin cv. ‘Bora’ phenolic compounds luteolin-7-O-glycoside and п-coumaric acid are predominated. The conclusion about possible use of Lavandin cv. ‘Bora’ for creation of food, cosmetic, therapeutic and preventive products is made.